2017
DOI: 10.1289/ehp1203
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Perfluoroalkyl and Polyfluoroalkyl Substances Concentration and Menstrual Cycle Characteristics in Preconception Women

Abstract: Background:Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are persistent synthetic chemicals that are widely used in industrial applications and often detectable in humans. In rats, PFASs can interfere with the estrous cycle. In humans, menstruation has been viewed as a proxy of female fecundity, and periodic menstruation plays a critical role in endometrial sloughing in the absence of pregnancy and in preparing for embryo implantation.Objectives:We investigated the association between PFAS exposure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 43 publications
2
42
5
2
Order By: Relevance
“…Plasma PFOA was measured at the Key Laboratory of Children's Environmental Health in Shanghai, China. The experimental materials and methods have been described previously 6 . The concentration of PFOA was detected from 50 μL of plasma.…”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…Plasma PFOA was measured at the Key Laboratory of Children's Environmental Health in Shanghai, China. The experimental materials and methods have been described previously 6 . The concentration of PFOA was detected from 50 μL of plasma.…”
Section: Methodscontrasting
confidence: 99%
“…Le et al 62 reported that a delayed and attenuated LH surge may be a direct cause of female reproductive senescence. Ovulation failure and protraction of dioestrus in PFOA(2) mice may be associated with premature ovarian insufficiency 8 and the increase in the time until pregnancy and even infertility 6,64 . To resolve this problem, further studies are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed analytical method has been described elsewhere [24]. In brief, PFAS concentrations were measured in 100 μl plasma using high-performance liquid chromate graphy/tandem mass spectrometry (HPLC/MS-MS; Agilent1290-6490, Agilent Technologies Inc., USA).…”
Section: Pfas Measurementmentioning
confidence: 99%